The first cavernicolous Leuctridae (Insecta: Plecoptera) nymph from Guizhou, China - Huo, Qing-Bo; Wang, Qi-Ming; Guo, Xiao-Lei; Rehman, Abdur; Yang, Yu-Ben; Du, Yu-Zhou (Zootaxa, 2022)
In this study, the first cavernicolous stonefly of China is reported from Guizhou Province, southwestern China. The morphological characteristics show that this species is a member of the genus Rhopalopsole Klapálek, 1912 (Plecoptera: Leuctridae). The pale coloration and the reduced compound eyes indicate that this species could be an obligate troglobitic taxon. The mtDNA COI barcode fragment of this species supports its assignment to Rhopalopsole and suggests it a distant relative to Rhopalopsole longispina Yang & Yang, 1991.